Incidental foreign vocabulary learning through multimodal exposure; the role of orthographic input - Bali, Persefoni (2024)
Incidental foreign vocabulary learning has mainly focussed on learning vocabulary through context. Recent research has shown that it is possible to acquire new foreign language vocabulary through multimodal situations without any prior knowledge of the foreign language. It has also shown that it is possible to learn the meaning of the words through the exposure to pictorial information. However, these studies focus on languages that use the same script. In this thesis, the multimodal situations were used with a language with a partially overlapping script (i.e. Greek). The study of partially overlapping scripts could shed light to less explored areas in incidental learning research and contribute to our understanding of the processes involved in foreign language learning. The aim of this thesis was to explore the impact of orthographic input on the incidental acquisition of foreign language vocabulary (both the auditory and the written form) in complete beginners in a foreign language. Participants were native English speakers without any prior knowledge of Greek.